The Angel of the Lord: a Biblical, historical, and theological study - Foreman, Matt (Waters of Creation, 2020)
Foreword: Michael S. Heiser -- Matt's preface -- Doug's preface -- Introduction: the Angel of the covenant -- The Angel and Biblical theology -- The Angel and church history -- The Angel in application -- Appendices -- Works Cited -- Author index -- Scripture index.